1999
DOI: 10.1007/s007050050592
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus infection modulates the expression of type IV collagenase in epithelial cells

Abstract: We investigated the effect of influenza A/Beijing/353/89 (H3N2) virus infection on the expression of type IV collagenase in two different types of epithelial cell. Depending on the cell line infected, the viral infection caused changes in the expression of type IV collagenase. The expression of matrix metalloproteinase-9 (MMP-9; 92 kDa) but not of matrix metalloproteinase-2 (MMP-2; 72 kDa) was stimulated in Vero cells. In MDCK cells, the MMP-2 production increased with the virus infection. According to the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…MMP-9 is known to be up-regulated in a variety of cells by many agents, including growth factors, cytokines, and viral proteins [15,22]. In a previous study, we also demonstrated that the influenza A virus modulates MMP-9 expression in epithelial cells [41]. As shown in the results of this study, MMP-9 was divergently regulated depending on the viruses.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…MMP-9 is known to be up-regulated in a variety of cells by many agents, including growth factors, cytokines, and viral proteins [15,22]. In a previous study, we also demonstrated that the influenza A virus modulates MMP-9 expression in epithelial cells [41]. As shown in the results of this study, MMP-9 was divergently regulated depending on the viruses.…”
Section: Discussionsupporting
confidence: 68%
“…Several reports have described the effect of host proteinase or its inhibitors on the viral infection and multiplication of paramyxoviruses [22,27,38]. We have also reported that the influenza A virus can modulate MMP-9 expression in epithelial cells [41]. Interestingly, the amino acid sequence at the N-terminus of the F1 protein (Gly-Ile/Leu), which is conserved among the paramyxoviruses [38], corresponds to the cleavage site of the substrate recognized by MMP [25].…”
Section: Introductionmentioning
confidence: 90%
“…Infection of epithelial cells with influenza induced MMP-2 mRNA expression [42] , while poly(I:C)-stimulated epithelial cells increased secretion of MMP-1, MMPs 8-10 and MMP-13 [36] . MMP-2 and MMP-9 are proteinases which are capable of degrading type IV collagen; thus, they are considered to play an important role in the degeneration of the epithelial cell layer [43] .…”
Section: Discussionmentioning
confidence: 99%
“…MMP dysregulation can affect tissue remodeling and organ homeostasis (38,65). In response to inflammation and cellular activation, MMPs are synthesized by a variety of cell types (4,49) including endothelial and epithelial cells (13,64), leukocytes (14,23,34,46), neural cells (38), and hepatocytes (47). Cytokines (11), cell differentiation (6,48,60), and viral infection (11,55) affect the regulation of MMPs.…”
mentioning
confidence: 99%